Conrad's shadow : catastrophe, mimesis, theory - Lawtoo, Nidesh (East Lansing : Michigan State University Press, 2016)
Lawtoo offers new readings of Joseph Conrad's novels and the postcolonial and cinematic works that respond to his oeuvre. Lawtoo argues that Conrad's fascination with doubles urges readers to reflect on the two sides of mimesis, that once joined, reveal Conrad's Janus-faced fictions as powerfully relevant to our contemporary world of global violence and environmental crisis.
pt. 1. Ethics of catastrophe -- Dueling to the end / ending 'The duel': Clausewitz avec Girard -- Ethical storms: Typhoon to 'The secret sharer' -- The cooperative community: epidemics in The shadow-line -- pt. 2. Anthropology of Frenzy -- A picture of Europe: possession trance in Heart of darkness -- A picture of Africa: postcolonial mimesis in Achebe's Things fall apart -- pt. 3. Metaphysics of tragedy -- Surrealist mimetism: fear of the dark in The nigger of the 'Narcissus' -- Rebirth of tragedy: Almayer's Folly to Apocalypse now -- Hypermimesis: horrorism redux in The secret agent -- Conclusion.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Conrad, Joseph, -- 1857-1924 -- Criticism and interpretation; Conrad, Joseph, -- 1857-1924; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Criticism, interpretation, etc